CALCULATION OF COMBUSTION AIR SUPPLY AND FLUE GASES AT INDIVIDUAL HEATING MULTI-STOREY APARTMENT BUILDINGS - , ЕЖИ, МАРЕК (Municipal economy of cities. Series: «Economy science», 2013)
The equation for determining the gravitational pressure in the individual heating-rise apartment buildings in the case where the air enters the combustion process of the stairwell of the building. An algorithm for calculating the flow combustion air and flue gases.